HIV and Pregnancy in Türkiye: Gaps and Gains in the Era of Modern ART: A Multicenter Cohort Study - Damar Cakirca, Tuba; Kurtaran, Behice; Aydin, Ozlem; Kayaaslan, Bircan; Kaya, Bulent; Karaoglan, Ilkay; Tasova, Yesim (Springer/Plenum Publishers, 2026)
We aimed to review perinatal outcomes in HIV-positive pregnant women and their infants, as well as Turkish clinicians' approaches to the management of HIV in pregnancy. This multicenter cohort study included pregnant women living with HIV (WLWH) across T & uuml;rkiye from 2010 to 2024. 209 pregnancies among 162 WLWH were identified. Nearly 90.9% were diagnosed before or during pregnancy, and 90% were on antiretroviral therapy (ART) at delivery. 150 women had viral loads of less than 1,000 copies/mL during labor. The most chosen ART combination during pregnancy was tenofovir/emtricitabine+raltegravir. Most common mode of delivery was cesarean section (78.9%). Among 174 deliveries, 22 (12.6%) were preterm. Regarding newborn prophylaxis, 137 (88.4%) received zidovudine and 34 received nevirapine. 14 infants were breastfed. No congenital malformation, neonatal or maternal mortality was observed. Overall, 13 infants were diagnosed HIV-positive, indicating an MTCT rate of 7.9% in this cohort. Breastfeeding (OR: 30.1, 95% CI: 4.70-193.50, p < .001) and absence of ART during pregnancy (OR: 30.9, 95% CI: 5.20-183.90, p < .001) were the most prominent variables affecting the infants' HIV positivity. Despite efficient preventative strategies announced over years, we report a high MTCT rate of 7.9%, aligning with previous literature from T & uuml;rkiye. The findings highlight that the absence of ART and breastfeeding remain critical risk factors for perinatal HIV transmission. This large real-world cohort, reflecting Turkish clinicians' practices, helps define major gaps in MTCT prevention in the modern ART era and provides valuable evidence to inform clinicians, policy makers, and public health strategies.
Keywords: HIV; Pregnancy; Vertical transmission; Women